Life tables of cashew stem and root borers, Plocaederus ferrugineus and Polcaederus obesus (Coleoptera: Cerambycidae) - Vasanthi, P.; Raviprasad, T.N. (Journal of Plantation Crops, 2014)
Cashew stem and root borers, Plocaederus ferrugineus L. and Plocaederus obesus Gahan are major pests of cashew (Anacardium occidentale). Life tables of these pests were constructed by rearing them on cashew bark under laboratory conditions. The population parameters such as, fecundity (ΣFx), net reproductive rate (Ro), cohort generation time (Tc), innate capacity to increase (rc), finite rate of population growth (λ) and doubling time (DT) were estimated. The larval stage in P. ferrugineus and egg stage in P. obesus were higher in contributing to the stable age distribution (Cx) of these pest species. The Ro for P. ferrugineus and P. obesus was 29.00 and 25.96, respectively. The finite rate of population growth (λ) was more than 1.0 for both the species, which indicated an increasing population. The doubling time for P. ferrugineus and P. obesus was 60.18 days and 70.21 days, respectively. The analysis of age-specific life table indicated that egg and early larval stages at 1 to 45 days of age showed high age-specific mortality (qx) and the later larval stages, aged 90 to 120 days showed high mean expectancy of life (ex). The population survival curves for both the species were comparable, with a sharp decline in the survival rate for early stages, indicating these were the most vulnerable stages.